Rancang Bangun Monitoring Lokasi Pesawat Menggunakan ADS-B dengan RTL-SDR dan Raspberry Pi - Diraputra, M Yoga Azto; Soim, Sopian; Sarjana, Sarjana (Protek : Jurnal Ilmiah Teknik Elektro, 2021)
Abstract Ã¢â‚¬â€ Automatic Dependent Surveillance Broadcast (ADS-B) is a surveillance technology that provides information on aircraft in the air in the form of 24 bit ICAO aircraft address, ident or squawk, massage, altitude, nationality, speed, longitude, track and heading. The problem faced now is that surveillance can only be done with a web and android-based application on FlightRadar24 so that if the user wants to display more aircraft information, the user is required to pay a subscription. To overcome this problem, hardware is needed that can receive ADS-B signals with a frequency of 1090 MHz and can translate them into information signals. RTL-SDR is hardware that can receive signals with a frequency range from 25 MHz - 1700 MHz, by applying the Raspberry Pi it is used to configure RTL-SDR as a receiver capable of receiving information from ADS-B signals. To get the maximum reception, an omnidirectional antenna is needed that can receive signals from all directions. With this system, it is expected to make it easier to monitor aircraft in real time and processing ADS-B signal data is determined by the strength and weakness of the signal that can be received by RTL-SDR.